Breastfeeding by Women Living With Human Immunodeficiency Virus in a Resource-Rich Setting: A Case Series of Maternal and Infant Management and Outcomes. (8th February 2019) - Nashid, N; Khan, S; Loutfy, M; MacGillivray, J; Yudin, M H; Campbell, D M; Barozzino, T; Baqi, M; Read, S E; Bitnun, A
Abstract: The reduction in human immunodeficiency virus (HIV) transmission through breastmilk with maternal combination antiretroviral therapy (cART) has led many pregnant women living with HIV and healthcare providers to question exclusive formula feeding in resource-rich settings. Here, we describe cART prophylaxis in 3 breastfed infants whose mothers had sustained virologic suppression; all 3 of these infants remained uninfected.